Students' Motivation and it's impact on English Language Learning Outcomes - Siti Mariyanah (PDPI (Perkumpulan Dosen Peneliti Indonesia), 2026)
Students’ motivation plays a crucial role in determining the success of English language learning outcomes. Motivation influences students’ engagement, persistence, and attitudes toward learning activities, which ultimately affect their academic achievement. This study aims to examine the impact of students’ motivation on English language learning outcomes. Using a quantitative approach, data were collected through motivation questionnaires and English achievement tests administered to students at the secondary education level. The data were analyzed using statistical techniques to identify the relationship between motivational factors and learning outcomes. The findings reveal that students with higher levels of intrinsic and extrinsic motivation tend to demonstrate better performance in English language skills, including reading, writing, listening, and speaking. The results also indicate that motivation significantly contributes to students’ willingness to participate actively in learning processes and to overcome learning difficulties. Therefore, enhancing students’ motivation should be a key focus for educators in designing effective English language instruction to improve learning outcomes.